Improving Efficiency of Wiecon Machine by Using Seven Tools and Value Engineering Methods at PT. Garudafood Putra Putri Jaya Gresik - Moch Choeszaini (Jurnal VOK@SINDO, 2014)
A production line is demanded with high productivity and efficiency as the increasing minimum wage regional. However, there were a lot of problems in the production line, especially in mixer wiecon line at PT. Garudafood Putra Putri Jaya Gresik. Value Engineering and Seven Tools methods were implemented to to solve the existing problems dealing with the efficiency in which Mixer Wiecon line was not able to reach the production target. Seven Tools method was applied to help identify the problems by using Ishikawa diagram as well as histogram. Value Engineering method was implemented to solve the identified problems through five steps: information step, speculation step, analysis step development step, presentation and follow-up step. Based on the result of the analysis of several alternatives proposed, the implementation of digital gauge with ultrasonic sensor on tempering machine has proven to be effective in solving the problems in Mixer Wiecon line. This gauge is then used because it is affordable to make for the company and it can give the largest amount of cost saving